2017
DOI: 10.1121/1.4982923
|View full text |Cite
|
Sign up to set email alerts
|

Input-output functions of the nonlinear-distortion component of distortion-product otoacoustic emissions in normal and hearing-impaired human ears

Abstract: Distortion-product otoacoustic emissions (DPOAEs) arise in the cochlea in response to two tones with frequencies f1 and f2 and mainly consist of two components, a nonlinear-distortion and a coherent-reflection component. Wave interference between these components limits the accuracy of DPOAEs when evaluating the function of the cochlea with conventional continuous stimulus tones. Here, DPOAE components are separated in the time domain from DPOAE signals elicited with short stimulus pulses. The extracted nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
0
28
1
1
Order By: Relevance
“…Exploiting the different latencies of the components, stimulation with short pulses instead of conventional continuous primary tones enables the separation of the DPOAE components in the time domain [5], which significantly increases the accuracy of DPOAEs when used to estimate behavioral thresholds [4,6]. However, there is evidence for additional components in the DPOAE recordings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploiting the different latencies of the components, stimulation with short pulses instead of conventional continuous primary tones enables the separation of the DPOAE components in the time domain [5], which significantly increases the accuracy of DPOAEs when used to estimate behavioral thresholds [4,6]. However, there is evidence for additional components in the DPOAE recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable phase shifts of the stimulus pulses in consecutive acquisition blocks enabled the cancelation of the stimulus pulses after ensemble averaging [13]. Details of the measurement setup and the short-pulse acquisition paradigm are specified elsewhere [6]. For comparison with simulated data, DPOAE components were extracted by fitting the zerophase band-pass filtered signal with a mathematical model using a least-squares approach [5].…”
Section: Er-10c Dpoae Probe-system (Etymotic Research Elkmentioning
confidence: 99%
“…The primary goal of this study is the comparison of two extraction methods of the nonlinear-distortion component in the time domain. The first method, referred to as onset decomposition (OD), 3,12 samples the envelope of p(t) at a time instant, T OD , before the coherent-reflection component starts to interfere to obtain an estimate of the amplitude,P OD , of the nonlinear-distortion component [ Fig. 1(a)].…”
Section: Dpoae Source Extractionmentioning
confidence: 99%
“…2 Recently, it was shown that the accuracy of the relationship between EDPTs and behavioral thresholds significantly increases when the amplitude of p 1 (t) is extracted from DPOAE time signals evoked by pulsed stimuli using a technique called onset decomposition (OD). 3 In contrast to previously established source separation methods, which rely on either time-consuming recordings of DP-grams with high frequency resolution 2,4 or chirps spanning a frequency range of octaves, 5,6 pulsed stimulation enables estimation of the two DPOAE components at a single f 2 frequency. 7 Utilizing short-pulsed DPOAE recordings, OD extracts the nonlinear distortion component without the necessity of using an individually adapted third tone to suppress the coherent-reflection component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation